KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DENGAN KECEPATAN TENDANGAN SABIT PADA ATLET PUTRA SENIOR PERSAUDARAAN SETIA HATI TERATAI DUTA KABUPATEN KAMPAR - Andra Suharsoyo; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: the problem of this research is that the capability of sickle kick speed is still not good, this is seen when the athletes perform a match and several factors that become cause the physical elements are not optimal, such as leg muscle explosive power. The kind of this research is correlational research that be used to compare two different variables in order to determine the relation level between those variables. The population in this research is Persaudaraan Setia Hati Teratai Duta Kabupaten Kampar martial arts athletes which amounts to 20 people. The sampling technique is used total sampling, where the total population is sampled. The purpose of this research is to determine the contribution of leg muscle explosive power with the sickle kick speed to Persaudaraan Setia Hati Teratai Duta Kabupaten Kampar martial arts atheletes. The instrument in this research is using vertical jump to leg muscle explosive power while the speed test was to measure the speed of a sickle kick. The test data is using the normality test, correlation moment product test, significant test α = 0,05. Variable normality test X, L0maks (0,16030) < Latbel(0,190), and variable normality test Y, L0maks (0,1621) < Ltabel (0,190) in other word the confidence level of 95% normal data and the conclusion of this research indicates where there is significant contribution between contribution of leg muscle explosive power with the sickle kick speed, with a correlation r = 0,640 where r count > r tabel or 0,640 > 0,456 with determination coefficient is 40,96%. The relationship is categorized as strong. Ha is accepted.Key Words: Contribution, Leg Muscle Explosive Power, Kick Speed